Beyond knowledge sharing: Withholding knowledge at work - Webster, J.; Brown, Graham; Zweig, D.; Connelly, C.; Brodt, S.; Sitkin, S. (2008)
This chapter discusses why employees keep their knowledge to themselves. Despite managers' best efforts, many employees tend to hoard knowledge or are reluctant to share their expertise with coworkers or managers. Although many firms have introduced specialized initiatives to encourage a broader dissemination of ideas and knowledge among organizational members, these initiatives often fail. This chapter provides reasons as to why this is so. Instead of focusing on why individuals might share their knowledge, however, we explain why individuals keep their knowledge to themselves. Multiple perspectives are offered, including social exchange, norms of secrecy, and territorial behaviors. © 2008 Emerald Group Publishing Limited.